Early Human Evolution Early Human Evolution of Indonesia at the Bandung Geological Museum in the Perspective of Science and Religion - Rizqy, Ade Vito (Mataram University, 2023)
The development of science over the progress of the times is not spared from the development of the theory of evolution based on natural selection and genetic influence. Human origins are studied from various sciences such as Biology, Geology, History, Sociology, and Religion based on mutually reinforcing perspectives. To examine more deeply in this study using the field study method to the Bandung Geological Museum and study literature. There are fossils found from Indonesia to Africa and Europe such as Homo erectus, Homo sapiens, Homo Habills, Australopithecus, etc. Become supporting evidence for the theory of evolution based on the physiology and anatomy of the body. That every period experiences different survival changes. Â